Utilizing relative ordered structure theory to guide polysaccharide purification for structural characterization. (June 2021) - Wang, Yu-Xiao; Yin, Jun-Yi; Zhang, Ting; Xin, Yue; Huang, Xiao-Jun; Nie, Shao-Ping
Abstract: While polysaccharides are the most abundant biomacromolecules widely distributed in nature, little is known in their chemical structures and functional mechanism. Compared with DNA and protein, polysaccharides possess more complex structures and composition with various molecular size, conformational shape and charge characteristic. Currently, the lack of a uniform and clear consensus of polysaccharide purity leads to low accuracy of structural analysis. In the present study, a new theory on polysaccharide purification named as "relative ordered structure" was proposed, which was used to purify the water-extracted polysaccharides from Hypsizygus marmoreus (SHMP), successfully giving five purified sub-fractions. Results showed that their major chemicals were similar, while molecular weights, monosaccharide compositions, surface morphology, solution properties as well as their structural features enormously varied. Methylation and 1D/2D NMR analysis indicated the presence of α-glucans, fucomannogalactans and galactoglucan in SHMP, further confirming the feasibility of this theory in isolation and purification of natural polysaccharides. Based on the results and previous reports, this work aims to introduce and generalize the "relative ordered structure" theory. Altogether, structural characterization of polysaccharides cannot simply "copy" the techniques on protein, more theories and methodology applicable to polysaccharide itself should be established. Graphical abstract: Image 1 Highlights: "Relative ordered structure" effectively guides the purification of complex polysaccharide. Five fractions were successfully purified from the water-extracted polysaccharides from H. marmoreus (SHMP). They presented different viscosities and structures with high sugar content and narrow M w distribution. SHMP contained α-(1→ 4)-glucans, fucomannogalactans and galactoglucans.